Brill's companion to the reception of Sophocles - Lauriola, Rosanna.; Dēmētriou, Kyriakos N. (Brill's Companions to Classical Reception, 2017)
Brill's Companion to the Reception of Sophocles offers a comprehensive account of the influence, reception and appropriation of all extant Sophoclean plays, as well as the fragmentary Satyr play The Trackers , from Antiquity to Modernity, across cultures and civilizations, encompassing multiple perspectives and within a broad range of cultural trends and manifestations: literature, intellectual history, visual arts, music, opera and dance, stage and cinematography. A concerted work by an international team of specialists in the field, the volume is addressed to a wide and multidisciplinary readership of classical reception studies, from experts to non-experts. Contributors engage in a vividly and lively interactive dialogue with the Ancient and the Modern, which, while illuminating aspects of ancient drama and highlighting their ever-lasting relevance, offers a thoughtful and layered guide of the human condition.